Development of Dy3+-doped Gd2MoB2O9 phosphor and their luminescence behavior. Issue 177 (2nd January 2017) - Ruengsri, S.; Insiripong, S.; Sangwaranatee, N.; Kim, H.J.; Wantana, N.; Angnanon, A.; Kaewkhao, J.
ABSTRACT: In this work, the Gd2 MoB2 O9 and Gd2 MoB2 O9 :Dy 3+ phosphors have been prepared by solid state reaction and their structural and luminescence properties have been studied. The Gd2 O3, MoO3, H3 BO3 and Dy2 O3 were used as starting materials and homogeneously mixed with appropriate ratio. The mixed materials were pressed at 20 tons and sintered at 800, 850, 900, 950, 1000, 1050 and 1100°C. The Gd2 MoB2 O9 phase was confirmed by X-ray diffractometer (XRD). The photoluminescence spectra measured by 257 nm excitation show one emission peak at 310 nm corresponding to 6 P7/2 → 8 S7/2 of Gd 3+, and four emission peaks of Dy 3+ at 478, 575, 663 and 754 nm corresponding to 4 F9/2 → 6 H15/2, 6 H13/2, 6 H11/2 and 6 H9/2 transitions, respectively. The chromaticity coordinates under excitation of λex = 352 nm are (0.48, 0.42), which lies in the white region of CIE 1931 chromaticity diagram. The radioluminescence property was studied by 50 kV, 30 mA X-ray irradiation and compared with commercial BGO crystal. It was found that the integral scintillation efficiency showed 76% of BGO. This result suggests that the developed phosphor may be used in W-LEDs and X-rays imaging applications.